Determinants of Repayment Performance in Indian Micro-Credit Groups - Deininger, Klaus; Liu, Yanyan (2012)
Despite their potential importance and ease of modification, impacts of monitoring and loan recovery arrangements on micro-credit groups' repayment performance have rarely been studied. Data on 3,350 expired group loans in 300 Indian villages highlight that regular monitoring and audits, high repayment frequency, consumption smoothing support through rice credit, and having group savings deposited with the lender all significantly increase repayment rates. Estimated magnitudes of their effects vastly exceed those of members' socio-economic characteristics. Significantly lower repayment on loans originating in externally provided grant resources suggests that stringent monitoring will be essential for these to have a sustainable impact.